Poster abstract: Smart-HOP: a reliable handoff procedure for supporting mobility in wireless sensor networks - Fotouhi, Hossein (2014)
This poster abstract presents smart-HOP, a reliable handoff mechanism for mobility support in Wireless Sensor Networks (WSNs). This technique relies on a fuzzy logic approach applied at two levels: the link quality estimation level and the access point selection level. We present the conceptual design of smart-HOP and then we discuss implementation requirements and challenges.